2013
DOI: 10.1038/aps.2013.75
|View full text |Cite
|
Sign up to set email alerts
|

Blocking TLR2 activity diminishes and stabilizes advanced atherosclerotic lesions in apolipoprotein E-deficient mice

Abstract: The pharmacologic or genetic blockade of TLR2 activity diminishes and stabilizes advanced atherosclerotic lesions in ApoE(-/-) mice. Thus, targeting TLR2 signaling may be a promising therapeutic strategy against advanced atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…8 On the other hand, blockade of TLR2 activity with the pharmacologic or genetic manipulations significantly reduced the plaque size, and increased plaque stability in the brachiocephalic arteries. 9 The protective effects of TLR2 antagonism were considered as associated with the suppression of the expression of pro-inflammatory cytokines IL-6 and TNF-a, and the inactivation of transcription factors NF-kB. Moreover, high-cholesterol diet more prominently accelerated atherosclerotic formation in ApoE -/mice.…”
Section: Discussionmentioning
confidence: 99%
“…8 On the other hand, blockade of TLR2 activity with the pharmacologic or genetic manipulations significantly reduced the plaque size, and increased plaque stability in the brachiocephalic arteries. 9 The protective effects of TLR2 antagonism were considered as associated with the suppression of the expression of pro-inflammatory cytokines IL-6 and TNF-a, and the inactivation of transcription factors NF-kB. Moreover, high-cholesterol diet more prominently accelerated atherosclerotic formation in ApoE -/mice.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 and 4 have been shown to be atherogenic, while conflicting research regarding TLR9’s involvement in CVD pathologies has been shown in the literature [ 87 ]. TLR2-deficient mice susceptible to CVD and in vitro studies using human cells which investigated atherogenicity of TLR have shown that TLR2 plays a role in regulating ROS-induced endothelial and vascular inflammation [ 190 ], plaque formation [ 191 ], migration of vascular smooth muscle cells from the tunica media to the intima [ 192 ], and influences plaque stability [ 193 ]. Comparable results have been demonstrated in studies involving TLR4, as TLR4 has been associated with endothelial and vascular inflammation [ 194 , 195 ] and atherosclerotic plaque formation [ 196 ], and increases macrophage, foam cell, and lipid content of plaques [ 196 , 197 , 198 , 199 ], hypertension [ 200 ], plaque rupture [ 201 ], and migration of vascular smooth muscle cells [ 202 ].…”
Section: Taurine the Innate Immune System And Potential Therapeumentioning
confidence: 99%
“…7 Using ApoE −/− atherosclerotic mice, other groups found that TLR2 activation by exogenous ligands increases atherosclerotic plaque size and neointima formation in femoral arteries, notably through promoting ROS production and smooth muscle cell migration in an IL-6 dependent manner. 1014 …”
Section: Emerging Concepts Of the Mechanisms Of Plaque Erosion: Rolesmentioning
confidence: 99%